Pemodelan dan Pembentukan Tabel Morbiditas-Mortalitas Stroke dan Penyakit Serebrovaskular dengan Model Multi Status Rantai Markov Waktu Kontinu - Andini Setyo Anggraeni; Nahrul Hayati (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2026)
Stroke and cerebrovascular disease are major health challenges in Indonesia, with morbidity and mortality rates influenced by age and gender. This study aims to model the and to construct a morbidity-mortality table based on age and gender. The method used is Continuous Time Multistate Markov Chain modeling, combined with flow equations, orientation equations, and integration equations to form a decrement table. Transition probabilities are calculated using Kolmogorov's forward differential equation. The results show that transition probability tables for men and women aged 20–90 years (t=1) are successfully formed and can be detailed down to a monthly or daily scale. Non-hemorrhagic stroke is the most common type of stroke, especially in healthy individuals aged over 40 years. Young hemorrhagic stroke patients are at high risk of recurrence, while men over 45 years are more susceptible to sequelae such as aphasia and hemiparasis, while women are at higher risk of non-hemorrhagic stroke. In patients with SNH, both men and women showed a sharp decline in the probability of recurrence after age 25, but the risk remained higher than for other types of stroke or sequelae. Stroke sequelae tended to persist in men until age 51 and in women until age 56, before declining. The risk of death within one year increased significantly with advancing age, with a dominant pattern of death from non-hemorrhagic stroke in men and hemorrhagic stroke in women. These findings provide important contributions to the health and actuarial world in planning interventions and managing stroke risk.